Meta-analysis of sustainable transport logistics trends - Johannes Dirnberger; Uwe Brunner (Logistics 4.0 and Sustainable Supply Chain Management: Innovative Solutions for Logistics and Sustainable Supply Chain Management in the Context of Industry 4.0. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 26, 2018)
In general, Austrian manufacturing companies need to catch up in terms of sustainable transport logistics. Awareness-raising on sustainability and a broad debate are necessary that companies rethink in this context. This paper, therefore, develops and applies a meta-analysis in order to analyze the development of transport logistics trends. This research integrates qualitative and quantitative elements of the content analysis. Firstly, existing trend analyses are evaluated and compared in order to subsequently define trend categories. Secondly, the identified trend categories are analyzed by a qualitative content analysis. Finally, a frequency analysis is performed to describe temporal developments. This meta-analysis evaluates how sustainability in terms of transport logistics has developed in comparison with other subject areas based on a prestigious, well-known international journal regarding logistics and traffic issues. Five relevant trends have been identified, their temporal development has been analyzed and a forecast has been created. Current transport logistics trend analyses usually do not challenge the topic of sustainability qualitatively by means of a meta-analysis. The validity of the definition whether a trend is relevant is increased, since the search items are analyzed in the context of previously defined trend categories. The meta-analysis is practically applicable, as in the period from 2014 to 2017 short-term and medium-term effects were tested in 171 editions of a subject-specific, but nonscientific international journal around logistics and traffic issues. This journal is published since 1945 and, therefore, comprehensively reflects the practical discussion about transport logistics.
urn:nbn:de:gbv:830-88223497; 10419/209195; https://econpapers.repec.org/RePEc:zbw:hiclpr:26
Keywords: 650; Meta-Analysis; Sustainability; Logistics; Trends